Cutaneous Malassezia: Commensal, Pathogen, or Protector? - Vijaya Chandra, Shree Harsha; Srinivas, Ramasamy; Dawson, Thomas L.; Common, John E. (Frontiers in Cellular and Infection Microbiology, 2021)
The skin microbial community is a multifunctional ecosystem aiding prevention of infections from transient pathogens, maintenance of host immune homeostasis, and skin health. A better understanding of the complex milieu of microbe-microbe and host-microbe interactions will be required to define the ecosystem’s optimal function and enable rational design of microbiome targeted interventions. Malassezia, a fungal genus currently comprising 18 species and numerous functionally distinct strains, are lipid-dependent basidiomycetous yeasts and integral components of the skin microbiome. The high proportion of Malassezia in the skin microbiome makes understanding their role in healthy and diseased skin crucial to development of functional skin health knowledge and understanding of normal, healthy skin homeostasis. Over the last decade, new tools for Malassezia culture, detection, and genetic manipulation have revealed not only the ubiquity of Malassezia on skin but new pathogenic roles in seborrheic dermatitis, psoriasis, Crohn’s disease, and pancreatic ductal carcinoma. Application of these tools continues to peel back the layers of Malassezia/skin interactions, including clear examples of pathogenicity, commensalism, and potential protective or beneficial activities creating mutualism. Our increased understanding of host- and microbe-specific interactions should lead to identification of key factors that maintain skin in a state of healthy mutualism or, in turn, initiate pathogenic changes. These approaches are leading toward development of new therapeutic targets and treatment options. This review discusses recent developments that have expanded our understanding of Malassezia’s role in the skin microbiome, with a focus on its multiple roles in health and disease as commensal, pathogen, and protector.